2015
DOI: 10.1108/aaouj-10-01-2015-b006
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study on a Flipped Classroom in Open University Teaching Based on an Ecological Perspective: A Case Study on a Translation Theory and Practice Course

Abstract: A flipped classroom refers toa model of learning which reverses how time is spent in and out of the class to shift the ownership of learning from the teachers to learners. But from the perspective of ecology, education can be healthily developed in a harmonious and dynamically-balanced ecological system. Therefore, this project, exemplified through translation teaching, constructed a flipped teaching model based on an ecological perspective that open university distance learners will adapt to after revisiting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 4 publications
(3 reference statements)
1
6
0
Order By: Relevance
“…This paper has illustrated how the flipped classroom model can be implemented practically both inside and outside the translation classroom. In line with the findings of Ling (2017), Mei (2017), andShu (2015) in translation training, this study's results of the test analysis also showed significant differences between the performance of the subjects over various learning activities and assessment tasks..…”
Section: Discussionsupporting
confidence: 89%
“…This paper has illustrated how the flipped classroom model can be implemented practically both inside and outside the translation classroom. In line with the findings of Ling (2017), Mei (2017), andShu (2015) in translation training, this study's results of the test analysis also showed significant differences between the performance of the subjects over various learning activities and assessment tasks..…”
Section: Discussionsupporting
confidence: 89%
“…This should be a principle that has been implemented throughout the school education process. 10 " This topic compares and analyzes the concepts, methods and effects of the current traditional teaching mode and open teaching mode in ordinary colleges and universities, and combines research methods such as literature analysis, observation analysis, questionnaire survey, comparative research, and induction. Cases and professional questionnaire surveys are carried out in three aspects, which specifically analyze the current status of environmental design majors in China's universities, find out the problems that need to be solved in the current environmental design majors, and strive to explore the open teaching mode of environmental design majors in universities to achieve improvement The training of environmental design talents in colleges and universities effectively promotes the integration of teaching concepts and teaching practices in ordinary colleges and universities.…”
Section: Introductionmentioning
confidence: 99%
“…The "flipped classroom" refers to flipping the teaching structure of "teachers teach in the classroom during the day and students do homework at home at night" and building a teaching structure of "students complete the internalization process of knowledge absorption and mastery in the classroom during the day and learn new knowledge at home at night". The teaching structure of "students complete the internalization process of knowledge absorption and mastery in the classroom during the day, and learn new knowledge at home at night" is a new classroom teaching structure that allows students to complete the internalization process of knowledge absorption and mastery in the classroom, and complete knowledge learning outside the classroom [15]. The author found that the interviewees did not have a correct understanding of the "so-called" flipped classroom after the interview.…”
Section: Discussionmentioning
confidence: 99%